Penggunaan Video Tutorial Pada Pembelajaran Keterampilan Membuat Patung Secara Daring - Riska Septian; Retno Winarni; Endang Wahyuningrum (Peneliti.net, 2022)
This research was conducted at SD Negeri 2 Kedungombo with a qualitative descriptive research in the form of a case study. The data in this study are in the form of a description of the use of video tutorials in learning to make sculptures for 6th grade students of SD Negeri 2 Kedungombo which were obtained through observation, interviews, and documentation methods. The research subjects in this study were the 6th grade students of SD Negeri 2 Kedungombo and the parents of the 6th grade students of SD Negeri 2 Kedungombo. The data collected was analyzed qualitatively. Planning the use of video tutorials in learning to make sculptures for grade 6 students of SD Negeri 2 Kedungombo online in detail is stated in the lesson plan (RPP), and the teacher provides video tutorials to students so that each student can download it via WA groups and share it to students so that students can play video tutorials on making sculptures whenever needed. The implementation of using video tutorials in learning to make sculptures for grade 6 students of SD Negeri 2 Kedungombo is easy, the content is easy to understand, the process is also coherent from beginning to end.